2019
DOI: 10.1103/physrevb.100.085119
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quantum spin Hall states in quasicrystals and crystals

Abstract: We theoretically study the quantum spin Hall states in an Ammann-Beenker-type octagonal quasicrystal and a periodic snub-square crystal, both sharing the same basic building blocks. Although the bulk states show significant differences in localization and transport properties, the topological phases manifest similarly in the two systems. This indicates the robustness of the topological properties regardless of symmetry and periodicity. We characterize the topological nature of the two systems with a nonzero to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Apparently, the NI and TI phases are divided by a curve of zero energy gap. In order to confirm the TPT, we calculated the spin Bott index, a topological 3 Research invariant we developed recently for TI systems with disorder [20][21][22]. It is found that there is a concomitant sharp jump in the spin Bott index B s across the phase boundary, confirming a TPT.…”
Section: Tpts In Crystals With Disordermentioning
confidence: 82%
See 2 more Smart Citations
“…Apparently, the NI and TI phases are divided by a curve of zero energy gap. In order to confirm the TPT, we calculated the spin Bott index, a topological 3 Research invariant we developed recently for TI systems with disorder [20][21][22]. It is found that there is a concomitant sharp jump in the spin Bott index B s across the phase boundary, confirming a TPT.…”
Section: Tpts In Crystals With Disordermentioning
confidence: 82%
“…We emphasize that the calculations cover almost all kinds of 2D crystalline lattices with different symmetries. More interestingly, the linear scaling is even applicable to quasicrystal lattices, as demonstrated by examples of Penrose-type pentagonal [20,21] and Ammann-Beenker-type octagonal [22] quasicrystalline lattices, as also shown in Figure 3. This points to a general linear scaling of TPT in all the 2D systems, regardless of not only lattice symmetry but also periodicity.…”
Section: Tpts In Crystal and Quasicrystal Latticesmentioning
confidence: 91%
See 1 more Smart Citation
“…1(b). In the previous works by Huang and Liu [28][29][30] , based on the Penrosetype quasicrystal lattice model described by the Hamiltonian (1), they proposed that the quantum spin Hall effect can be realized in quasicrystal lattices.…”
Section: Model and Methodsmentioning
confidence: 99%
“…Recently, the QSH effect is also explored in quasicrystals [39][40][41] by one of the authors. As shown in Fig.…”
Section: Quantum Spin Hall Statesmentioning
confidence: 99%